2015
DOI: 10.1073/pnas.1422336112
|View full text |Cite
|
Sign up to set email alerts
|

BDNF pro-peptide actions facilitate hippocampal LTD and are altered by the common BDNF polymorphism Val66Met

Abstract: SignificanceBrain-derived neurotrophic factor (BDNF) is a neurotrophin that elicits biological effects on synaptic plasticity. BDNF is initially synthesized as precursor proBDNF, and then the BDNF pro-peptide is simultaneously produced from the precursor protein. However, the physiological functions of the pro-peptide are largely unknown. Here, we demonstrate that the BDNF pro-peptide is a facilitator of hippocampal long-term depression (LTD), requiring the activation of GluN2B-containing NMDA-type receptors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
117
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(127 citation statements)
references
References 45 publications
6
117
0
Order By: Relevance
“…In the present study, we showed that the BDNF pro-peptide, when pre-incubated with BDNF, attenuated the ability of BDNF to inhibit hippocampal LTD and this inhibition was not rescued by treatment with a REX p75 NTR antagonist. Recently, we reported that the BDNF pro-peptide facilitates hippocampal LTD, and this enhancement requires p75 NTR , while BDNF successfully rescued hippocampal LTD [15]. Taken together with our recent report [15], the electrophysiological data shown in Figure 3 raise a possibility that the BDNF pro-peptide may interact directly with BDNF and thereby inhibit its availability.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the present study, we showed that the BDNF pro-peptide, when pre-incubated with BDNF, attenuated the ability of BDNF to inhibit hippocampal LTD and this inhibition was not rescued by treatment with a REX p75 NTR antagonist. Recently, we reported that the BDNF pro-peptide facilitates hippocampal LTD, and this enhancement requires p75 NTR , while BDNF successfully rescued hippocampal LTD [15]. Taken together with our recent report [15], the electrophysiological data shown in Figure 3 raise a possibility that the BDNF pro-peptide may interact directly with BDNF and thereby inhibit its availability.…”
Section: Discussionsupporting
confidence: 70%
“…Recently, we reported that the BDNF pro-peptide facilitates hippocampal LTD, and this enhancement requires p75 NTR , while BDNF successfully rescued hippocampal LTD [15]. Taken together with our recent report [15], the electrophysiological data shown in Figure 3 raise a possibility that the BDNF pro-peptide may interact directly with BDNF and thereby inhibit its availability. When present and functioning independently, both proteins (BDNF and its pro-peptide) could engage in their own separate biological activities.…”
Section: Discussionsupporting
confidence: 70%
“…Sortilin, another Vps10p receptor, is responsible for intracellular trafficking of newly synthesized proBDNF via its physical interaction with the region of BDNF pro-domain in which the Val66Met substitution resides [34]. BDNF Val66Met has been associated with risk for AD [35] and AD-related intermediate phenotypes [36], albeit inconsistently, and is thought to be an important factor in modulating neuroplasciticty [10]. Our results may provide insight into the inconsistent literature on the effects of BDNF Val66Met (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it was recently shown that BDNF administration in iPSC-derived neuron cultures up-regulates SORL1 expression in a SORL1 -genotype dependent manner [8]. The BDNF Val66Met polymorphism determines the activity-dependent secretion of BDNF [9] and also the function of the BDNF pro-peptide in facilitating neuroplasticity (LTD) [10]. As such, BDNF Val66Met may serve as a functional assay for BDNF activity in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms include activity-dependent effects on BDNF mRNA abundance and protein synthesis [32], secretion of BDNF from neurons [33], BDNF transcript and protein breakdown [32], post-translational modification from pro- to mature forms of BDNF [34], gene polymorphisms [35], epigenetic modifications [36] subcellular compartmentalization [37], interactions between BDNF signaling and other signaling pathways [38, 39]. Another mechanism can now be added to this list: down-regulation of BDNF mRNA by antidromic firing.…”
Section: Discussionmentioning
confidence: 99%